Shostakovich's preludes and fugues : contexts, style, performance - Mazullo, Mark, 1967- (JSTOR EBA., 2010)
This is a book-length study in English of Shostakovich's largest work for piano, the 'Twenty-Four Preludes and Fugues, Opus 87'. Mazullo describes the cultural contexts in which Shostakovich composed, relates the cycle to numerous piano works, and offers individual commentaries on each of the preludes and fugues.